Cost-effectiveness of an internet-based aftercare intervention after inpatient treatment in a psychosomatic hospital - Moessner, Markus; Bauer, Stephanie; Özer, Fikret; Wolf, Markus; Zimmer, Benjamin; Kordy, Hans (Psychotherapy research, 2014)
Objective: The implementation of new interventions into routine care requires the demonstration of both their effectiveness and cost-effectiveness. Method: We explored the cost-effectiveness of an Internet-based aftercare program in addition to treatment as usual (CHAT) which was compared to treatment as usual (TAU) following inpatient treatment. Incremental cost-effectiveness ratios were calculated based on cost of the intervention, cost of outpatient treatment, and remission rates within 1 year after discharge from hospital. Results: Assuming a willingness-to-pay of an additional 14.87 € per treatment for every additional percent of remission, CHAT was cost-effective against TAU at a 95% level of certainty. Cost per remission equaled 2664.84 € in TAU and 1752.75 € in CHAT (34.2% savings). Conclusions: This is the first evidence that Internet-based aftercare may enhance long-term treatment outcome in a cost-effective way.